2022
DOI: 10.3389/fvets.2022.933038
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of diets with omega-3 long-chain polyunsaturated fatty acids enhances feedlot performance, intramuscular fat content, fat melting point, and carcass characteristics of Tattykeel Australian White MARGRA lambs

Abstract: Meat eating quality indices such as intramuscular fat content (IMF) and fat melting point (FMP) of the Longissimus thoracis et lumborum muscle and the feedlot performance, carcass traits, and commercial wholesale cuts of lot-fed Tattykeel Australian White (TAW) MARGRA lambs as a result of dietary fortification of the diet with omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) were evaluated. A total of 75 TAW MARGRA lambs at 6 months of age with an average liveweight of 30 ± 1.2 kg were used. The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…The results of the current study agree that the decrease in the coefficient of nutritional conversion in Table (2) for the coefficients T1 and T2 with the findings of [18] which found that when lambs fed an Omega-3 diet put on the maximum weight, gaining 230 g/head/ day, compared to 224 g/head/day for lambs fed whole grain pellets (MSM) and 194 g/head/day for controls (p≤0.0390). As a result of Omega-3 intake to livestock, the higher average daily gain with lower feed intake suggests better nutrient utilization from the abomasum, either as a result of altered rumen ecology and environment that favors less bio hydrogenation and more by-pass proteins from the rumen or as a result of a higher rate of turnover of volatile fatty acid absorption [3].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the current study agree that the decrease in the coefficient of nutritional conversion in Table (2) for the coefficients T1 and T2 with the findings of [18] which found that when lambs fed an Omega-3 diet put on the maximum weight, gaining 230 g/head/ day, compared to 224 g/head/day for lambs fed whole grain pellets (MSM) and 194 g/head/day for controls (p≤0.0390). As a result of Omega-3 intake to livestock, the higher average daily gain with lower feed intake suggests better nutrient utilization from the abomasum, either as a result of altered rumen ecology and environment that favors less bio hydrogenation and more by-pass proteins from the rumen or as a result of a higher rate of turnover of volatile fatty acid absorption [3].…”
Section: Resultssupporting
confidence: 90%
“…During the winter, Omega 3 PUFAs act as mediators of thermogenesis [5]. Omega-3 fatty acids help maintain body temperature under environmental stress condition [18]. It is well known that dietary Omega-3 has an important role in producing eicosanoids, which regulate body temperature.…”
Section: Physiological Vital Indicatorsmentioning
confidence: 99%
“…Clinical studies have shown that long-term ω-3 PUFA supplementation can increase muscle mass in healthy individuals without increasing adiposity [ 77 , 78 ] and can slow or even prevent muscle atrophy under pathological conditions [ 79 , 80 ]. Similarly, ω-3 PUFA supplementation to meat animals increased carcass weight, lean muscle yield, and size of individual meat cuts without increasing carcass fat [ 81 , 82 ]. Supplementing ω-3 PUFA-rich fish oil also preserved muscle growth rates in lambs during prolonged heat stress by circumventing systemic inflammation [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%